Effect of variety and surface of Ripeness on Banana Springs - Norjannah Rahamathullah (2015)
This study was conducted to study the effect of variety, stage of ripeness on the quality of banana spring. The effect of frying and variety on the crispiness of banana was also evaluated. From the investigation it was noticed that Nangka banana was found better in respect of sweetness and texture. Only the green matured banana of both the varieties was suitable for preparation of banana springs. Frying for 5 minutes was sufficient for producing good quality (crispiness, odour and overall accepatability by consumers) of banana spring, especially from Nangka banana. Nangka banana spring were significantly crispier compared to Berangan banana spring due to its good physicochemical properties. While sensory evaluation test showed that Nangka banana spring fried at 5 minutes have a high potential to be marketed as banana spring.